Irrigation Regime, Irrigation Methods and Watering Techniques in Armenia - Muradyan, Mary («Տիր» հրատ.)
This article presents the irrigation regimes, norms and watering norms of some crops in Armenia and the importance of their correct choice in increasing productivity. Special attention was paid to determining the correct irrigation regime and selecting irrigation methods for various crops, considering their characteristics. This article aims to determine the feasibility of irrigation methods for various crops based on the calculations of irrigation norms. To achieve the goal, the task was to analyze the amount of precipitation in different geographical zones in Armenia, calculate irrigation and watering norms with the example of different crops, and consider the feasibility of the main irrigation methods. Statistical and analytical methods were implemented to study the irrigation field in Armenia. As a result, it was revealed that the choice of the correct irrigation regime and methods contributes not only to the increase of yields but also to water resource saving. Հոդվածում ներկայացված են Հայաստանում մի շարք գյուղատնտեսական մշակաբույսերի ջրման և ոռոգման նորմերը, ոռոգման ռեժիմը և դրանց ճիշտ ընտրության կարևորությունը մշակաբույսերի բերքատվության բարձրացման գործում, որով էլ պայմանավորված է սույն հոդվածի արդիականությունը։ Առաջնային ուշադրություն է դարձվել ոռոգման ճիշտ ռեժիմի սահմանմանը, ոռոգման մեթոդների ընտրությանը՝ հաշվի առնելով մշակաբույսերի առանձնահատկությունները։ В статье представлены нормы полива и орошения некоторых сельскохозяйственных культур в Армении, режим орошения и важность их правильного выбора в повышении урожайности, чем и обусловлена актуальность статьи. Основное внимание уделялось определению правильного режима орошения, подбору способов орошения с учетом особенностей сельскохозяйственных культур.
Keywords: Ecology